Adaptive Sliding Mode For Indirect Field Oriented Controlled Of Induction Motor - Patakor, Fizatul Aini; Sulaiman , Marizan; Ibrahim, Zulkifilie (2011)
In this paper, an adaptive Sliding Mode Control (SMC) for indirect field oriented control of three-phase induction motor is proposed. First, a sliding mode controller with integral sliding surface is designed. Then, an adaptive function of sliding gain is introduce to reduce the control effort of the SMC, so that there is no need to calculate the upper bound of the system uncertainties, as in traditional SMC. Finally the smooth function is applied to reduce chattering problem across the sliding surface. The speed control for the induction motor using the proposed control scheme is illustrated and the theoretical analysis for the adaptive SMC are described in detail. The results show that the proposed controller provides high performance characteristics and robust with regard to parameter variation and load disturbances. The effectiveness of the proposed scheme is verifying using MATLABISIMULINK.